Deformation Characteristics and Control Measures for Deep Foundation Pit in Soil–Rock Composite Strata in the Guangzhou Area - Lianyan Jia; Jinhuan Zhu; Zhiqi Wang; Xiaoyan Liu (Advances in Civil Engineering)
Geological conditions and supporting structures are critical factors influencing the deformation characteristics of deep excavations. This study investigates the deformation characteristics and corresponding control measures for typical deep excavations, focusing on a metro station excavation within a mixed soil–rock stratum in Guangzhou. Using field measurement data collected during the excavation phase, we perform a statistical analysis to examine the relationship between maximum deformation and various influencing factors, including excavation depth, spatial effects, and the insertion ratio of the support structure. Additionally, we explore the distribution of excavation deformations, the relationship between lateral and vertical displacements, and deformation modes, offering engineering recommendations for optimization. Our analysis shows that, due to significant variations in the thickness of soft soil layers in Guangzhou, the maximum lateral displacement of the support structures predominantly ranges from 15 to 30 mm, while vertical ground deformations range from 0.86‰ to 2.35‰ of the excavation depth. Increasing the insertion ratio of the support structures improves their stiffness and reduces surface settlement caused by excavation. However, when the base of the support structure is embedded in the load-bearing rock layer and the insertion ratio exceeds 0.25, further increases in the insertion ratio lead to diminishing returns in controlling surface settlement. Both vertical ground deformations and lateral displacements of the support structures are positively correlated with excavation depth, while negatively correlated with the length-to-width ratio, width-to-depth ratio, and insertion ratio of the excavation. Based on these findings, we propose construction measures to enhance the stability of deep excavations and protect adjacent structures.